PENGARUH HIDROTERAPI (RENDAM KAKI AIR HANGAT) TERHADAP PENURUNAN TINGKAT KECEMASAN PADA LANSIA DI DESA SUMBERSARI KECAMATAN MAESAN KABUPATEN BONDOWOSO TAHUN 2014 - Andi Eka Pranata (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2014)
This study aims to determine the effect of hydrotherapy (soaking feet of warm water) on reducing anxiety levels in the elderly in Sumbersari Village, Maesan District, Bondowoso District in 2014. Anxiety is a condition that is often experienced by the elderly because it is a degenerative process of the entire system including cognition and cognition. Hydrotherapy is a therapy that aims to provide and increase the sensation of relaxation for the human body.This study is a comparison with a quasi-experimental design with a non equivalent control group design approach. The study was conducted in Sumbersari Village precisely in Krajan II and Ekapradja Hamlets with a population of 100 people who met the criteria. While the sample used was 80 people using cluster sampling with details of 40 control groups and 40 intervention groups. The study looked at the difference between the degree of anxiety between pre and post in the control and intervention groups with the Wilcoxon Macth Paired Test analysis test, as well as the difference in post-treatment anxiety levels between the control group and the intervention group with the Mann Whitney analysis test. The analysis test uses a 95% confidence level. From this study, the results showed that there is an effect of hydrotherapy (soaking feet of warm water) on reducing anxiety levels in the elderly. This is indicated by the value of p = 0.021. P <α is 0.021 <0.05 so that Ho is rejected. Hydrotherapy has a relaxing effect that causes all constricting activities in the human body to decrease, thereby increasing calm and directly reducing anxiety.